Toward a causal model of chronic back pain: Challenges and opportunities - Huie, J. Russell; Vashisht, Rohit; Galivanche, Anoop; Hadjadj, Constance; Morshed, Saam; Butte, Atul J.; Ferguson, Adam R.; O'Neill, Conor (Frontiers in Computational Neuroscience, 2023)
Chronic low back pain (cLBP) afflicts 8.2% of adults in the United States, and is the leading global cause of disability. Neuropsychiatric co-morbidities including anxiety, depression, and substance abuse- are common in cLBP patients. In particular, cLBP is a risk factor for opioid addiction, as more than 50% of opioid prescriptions in the United States are for cLBP. Misuse of these prescriptions is a common precursor to addiction. While associations between cLBP and neuropsychiatric disorders are well established, causal relationships for the most part are unknown. Developing effective treatments for cLBP, and associated co-morbidities, requires identifying and understanding causal relationships. Rigorous methods for causal inference, a process for quantifying causal effects from observational data, have been developed over the past 30 years. These methods specify a minimal set of knowledge or “constraints” on the causal structure (for example, temporal order), identify causal structures that are consistent with these constraints, and then use data to rule out causal structures as possible. In this review we first discuss the conceptual model of cLBP that current treatments are based on, and how gaps in causal knowledge contribute to poor clinical outcomes. We then present cLBP as a “Big Data” problem, and identify how advanced analytic techniques may close knowledge gaps and improve clinical outcomes. We will focus on causal discovery, which is a data-driven method that uses artificial intelligence (AI) and high dimensional datasets to identiy causal structures, discussing both constraint-based (PC and Fast Causal Inference) and score-based (Fast Greedy Equivalent Search) algorithms.